Diarrhetic Shellfish Toxins and Other Lipophilic Toxins of Human Health Concern in Washington State - Vera Trainer; Leslie Moore; Brian Bill; Nicolaus Adams; Neil Harrington; Jerry Borchert; Denis Da Silva; Bich-Thuy Eberhart (Marine Drugs, 2013)
The illness of three people in 2011 after their ingestion of mussels collected from Sequim Bay State Park, Washington State, USA, demonstrated the need to monitor diarrhetic shellfish toxins (DSTs) in Washington State for the protection of human health. Following these cases of diarrhetic shellfish poisoning, monitoring for DSTs in Washington State became formalized in 2012, guided by routine monitoring of Dinophysis species by the SoundToxins program in Puget Sound and the Olympic Region Harmful Algal Bloom (ORHAB) partnership on the outer Washington State coast. Here we show that the DSTs at concentrations above the guidance level of 16 μg okadaic acid (OA) + dinophysistoxins (DTXs)/100 g shellfish tissue were widespread in sentinel mussels throughout Puget Sound in summer 2012 and included harvest closures of California mussel, varnish clam, manila clam and Pacific oyster. Concentrations of toxins in Pacific oyster and manila clam were often at least half those measured in blue mussels at the same site. The primary toxin isomer in shellfish and plankton samples was dinophysistoxin-1 (DTX-1) with D. acuminata as the primary Dinophysis species. Other lipophilic toxins in shellfish were pectenotoxin-2 (PTX-2) and yessotoxin (YTX) with azaspiracid-2 (AZA-2) also measured in phytoplankton samples. Okadaic acid, azaspiracid-1 (AZA-1) and azaspiracid-3 (AZA-3) were all below the levels of detection by liquid chromatography tandem mass spectrometry (LC-MS/MS). A shellfish closure at Ruby Beach, Washington, was the first ever noted on the Washington State Pacific coast due to DSTs. The greater than average Fraser River flow during the summers of 2011 and 2012 may have provided an environment conducive to dinoflagellates and played a role in the prevalence of toxigenic Dinophysis in Puget Sound.